Physiological characterization of winter canola under heat and drought stress during flowering and pod-filling stages - Pokharel, Meghnath (Kansas State University, 2020)
Canola (Brassica napus L.), also known as oilseed rape or double low rapeseed, is an economically valuable oilseed and an emerging bio-energy crop. Global climate models predict a significant increase in both day time and night time temperatures and erratic rainfall patterns at the global and regional scales, which can induce both yield and quality losses in winter canola. Three studies were conducted with an overall goal to quantify the impact of abiotic stress exposure during flowering and pod-filling stages in winter (biennial) canola. In the first study, the impact of high night temperature (HNT) exposure during flowering and pod-filling stages on the time-of-day of flowering, physiological traits, yield, oil content and seed fatty-acid composition were quantified. Two independent HNT stress experiments involving ten (experiment 1) and six (experiment 2) canola cultivars were conducted using walk-in climate-controlled environment chambers following a split-plot design. The results from both experiments demonstrated that peak flower opening shifted towards earlier hours in the morning. The photochemical efficiency of Photosystem (PSII) was significantly decreased and thylakoid membrane damage was significantly increased in the leaves of susceptible cultivars. Quantitative impact of heat stress was confirmed with increased sensitivity to HNT exposure from gametogenesis until maturity resulting in a significantly higher yield loss compared to stress exposure from post-flowering until maturity. HNT significantly decreased oil concentration, but increased protein concentration and saturated fatty acid levels in seeds of the susceptible cultivars. However, HNT had no impact on the unsaturated fatty acids in both hybrids and open-pollinated cultivars. Our findings conclude that canola hybrids are better suited to regions experiencing heat stress compared to open-pollinated cultivars. The second study was conducted to quantify the effect of HNT, high day time (HDT) and a combination of high day and night temperature (HNDT) stress on the reproductive processes during flowering, affecting yield, oil content and seed fatty-acid composition in winter canola through two independent experiments using walk-in climate-controlled environment chambers. Based on the results, HDT had the most significant impact on seed-set during flowering. HDT stress significantly shifted flowering towards early morning hours, induced floral sterility, flower abortion and complete loss of yield with two weeks of stress imposition during flowering. However, total dry matter accumulation, total number of pods, pods and seed weight per plant were significantly increased or unchanged which demonstrated significant plasticity in canola to overcome short episodes of HDT damage. Long duration heat stress under field conditions recorded significant decreases in pod number, grain yield and oil concentration. The impact of drought stress on the effective quantum yield of photosystem II and yield components was assessed during reproductive stages using field based rain-out shelters. Drought stress had a significant negative impact on quantum yield of photosystem II, biomass and the yield components in winter canola. Collectively, the findings from these studies indicate the possibility of using canola hybrids in regions that are currently faced with warmer climate and support breeding efforts towards developing winter canola with enhancing resilience to abiotic stresses under future warming scenarios.
Keywords: High night temperature stress; High day temperature stress; Drought stress; Flowering; pod filling; Winter canola